Kajian Analisis Struktur Komunitas Mangrove di Muara Jenggalu Kota Bengkulu - Nella Tri Agustini; Ayub Sugara; Samsul Bahri (Jurnal Laot Ilmu Kelautan, 2023)
This research was carried out in September 2022 at Muara Jenggalu, Bengkulu City. The mangrove vegetation in Muara Jenggalu, Bengkulu City consists of 8 (eight) true mangrove species : Avicennia alba, Avicennia marina, Bruguiera gymnorrhiza,Lumnitzera littorea, Rhizophora apiculata, Sonneratia alba, Sonneratia caseolaris and Xylocarpus granatum. Associated mangrove species consist of 3 (three) species, namely Nypa Fruticans, Hibiscus tiliaceus L, and Pandanus tectorius.The most common types of mangroves found in the Jenggalu Estuary, Bengkulu City, are Rhizophora apiculata and Sonneratia alba. The density of mangrove species in Muara Jenggalu, Bengkulu City, is categorized as rare, with a density value of mangrove species ≤ 1,000 ind/ha. Coverage of mangrove species in Muara Jenggalu is 69.59-86.27%. The lowest type of closure is 0.18-49.68%. The type of mangrove with the highest IVI in Muara Jenggalu, namely Sonneratia alba, plays an important role in the mangrove area of Muara Jenggalu with an IVI range of ≥ 121.55-163.28. The dominance index ranged from 0.45-0.78, and the diversity index (H') ranged from 0.34-0.93.